The Association Between Tobacco Marketing mix And Smoking Behavior Among Working Age Male Group In East Borneo, Indonesia - Nida Amalia (Jurnal Ilmu Kesehatan, 2018)
Background: Indonesia have implemented various antismoking measures since the prevalence of smoking were reported highest in Indonesia (46.16%) among ASEAN. However, major studies has not been carried out to measure that effect. The objective of this study was to determine the prevalence and characteristics of smoking and the influence of tobacco marketing mix factors (price, product, place and promotion) on smoking behaviors among working age males in Indonesia. Method: This cross sectional study was conducted in 2016. A total of 311 working age males was randomly selected from 10 sub - districts in urban areas of Samarinda, East Kalimantan, Indonesia to response a structured questionnaire. Data was transferred to STATA (Version 13, Stata Corporation, College Station TX) for analysis. The categorical data was reported as numbers and percentages. Bivariate analysis was performed to measures the estimated the association between each independent variable of interest and smoking behavior. Result: A total of 311, prevalence of smokers was 45.6% (95% CI: 40.09% to 51.23%). There are number and percentage related tobacco marketing mix factors such as Noticed advertisement or cigarette promotion (192, 61.7%), free sample of cigarettes (11, 3.5%), cigarettes at sale prices (42, 13.5%), special discount (73, 23.5%), free gifts (197, 63.3%), clothing or other items with a cigarettes (161, 51.8%), brand or logo (cigarette) (134, 43.1%), cigarette promotion in the mall (231, 74.3%), cigarette promotion in the television (173, 55.6%), cigarette promotion in radio (73, 23.5%). Conclusion: Tobacco marketing mix factors has two content that associated with smoking behavior such as notices advertisement or cigarette promotion (OR: 0.74, 95% CI: 0.46 to 1.18) and free sample of cigarettes was factor that associated with smoking behavior in working age males group (OR: 0.67, 95% CI: 0.39 to 1.15).